Penerapan Metode Ahp Untuk Penentuan Penerima Beasiswa (Study Kasus AMIK Depati Parbo Kerinci) - ROSY DASMITA (DEPATI PARBO PRESS, 2018)
ABSTRACT in accordance with regulations prescribed by the Kopertis to obtain a scholarship, then the required criteria to determine who will be selected to receive scholarships. Scholarships awarded to students to help someone less capable or accomplished during his studies to take. To assist in determining a person's determination would be eligible for a scholarship is needed a support system keputusan.Salah one method that can be used for Decision Support System is to use AHP (Analytical Hierarky Proces). This research will be appointed a case of finding the best alternative Based on criteria that have been determined by use traditional AHP method in that case. This method was chosen because it is able to select the best alternative from a number of alternatives, in this case meant that alternatives are eligible to receive scholarships based on specified criteria. Research carried out by finding the weights for each attribute, then do the ranking that will determine the optimal alternative, which is the best student. Keywords: Decision Support Systems, Applications and Software AHP Method Expert Choice